Planar Position Sensor Based on Mono Sensing Electrode and Hybrid-Frequency Excitation - Hongxiang Yu; Yu Zhang; Mengfeng Shen; Hongli Zhang; Zhao Gao; Dongyun Wang (Sensors, 2016)
A new way of measuring planar position for micrometric and sub-micrometric applications is presented with a mono sensing electrode and hybrid-frequency excitation. The sensing theory and operation principle are described and summarized, and a printed circuit board (PCB) sensor prototype is built and tested. It is shown by the experimental results that a very simple structure and geometric relationship are achieved. Meanwhile, displacement sensitivity on an order of 1.50 mV per micron and measurement repeatability better than 0.002 mm are easily fulfilled for a square zone of 256 mm2, making it a valuable alternative measurement device candidate for flexible and low-cost planar position detection.